IL-6 receptor blockade corrects defects of XIAP-deficient regulatory T cells - Wan-Chen Hsieh; Tzu-Sheng Hsu; Ya-Jen Chang; Ming-Zong Lai (Nature Communications, 2018)
XLP-2 syndrome is caused by XIAP mutation. Here the authors show that mouse and human XIAP-deficient regulatory T cells have defective suppressive function as a result of conversion to proinflammatory cytokine producing cells, an effect that can be prevented by blocking the IL-6 receptor.